An exploratory study of responsible gambling behaviour - Harris, Cheyne (Rhodes University, Faculty of Humanities, Department of Psychology, 2007)
In light of the findings of a pilot study by this researcher, entitled a study of the behaviour and strategies of responsible gamblers, it is vital that responsible gambling behaviour in the Eastern Cape be researched more thoroughly. The pilot study found that many ordinary gamblers experience cognitive distortions which may predispose them to varying levels of gambling problems, as well as specific biographical attributes that may determine such an outcome. The present study aims to address the limitations and recommendations put forward by the pilot study, namely its relatively small scale, and lack of generalisability as a result of sampling from a single gambling population. This project set out to assess gambling behaviour, and more so responsible gambling practices, to be able to conclude how, and in what form, responsible gambling takes place. The research was conducted USll1g a sample of one-hundred-and-thirty-seven gamblers from Hemingway's Casino in East London to develop data and establish norms on general gambling behaviour over a week, by administration of a survey questionnaire. The analysis of the data focussed on areas such as the link between gender and gambling behaviour, amount earned and amount spent on gambling, age and gambling trends as well as belief in luck and chances to win. Finally, the strategies (if any) used by gamblers to avoid problem gambling or overspending were assessed, and described by the gamblers themselves, and added to the results of the research. The results indicate that the majority of gamblers in the Eastern Cape are responsible, but many do still exhibit cognitive distortions and other behaviours that might put them at risk for problem gambling. With these results it is possible to provide basic data and information about the nature of gambling in the East London area that can be added to previous (as well as subsequent) studies, in order to build a clearer and more representative picture of the gambling situation in the Eastern Cape, South Africa.
Keywords: Gambling -- Case studies -- South Africa -- Eastern Cape; Gambling -- Social aspects -- South Africa -- Eastern Cape; Gambling -- Economic aspects -- South Africa -- Eastern Cape; Gambling -- Psychological aspects -- South Africa -- Eastern Cape